D3 dopamine receptor-preferring [11C]PHNO PET imaging in Parkinson patients with dyskinesia. (19th January 2016) - Payer, Doris E.; Guttman, Mark; Kish, Stephen J.; Tong, Junchao; Adams, John R.; Rusjan, Pablo; Houle, Sylvain; Furukawa, Yoshiaki; Wilson, Alan A.; Boileau, Isabelle
Abstract : Objective: To investigate whether levodopa-induced dyskinesias (LID) are associated with D3 overexpression in levodopa-treated humans with Parkinson disease (PD). Methods: In this case-control study, we used PET with the D3 -preferring radioligand [ 11 C]-(+)-PHNO to estimate D2/3 receptor binding in patients with levodopa-treated PD with LID (n = 12) and without LID (n = 12), and healthy control subjects matched for age, sex, education, and mental status (n = 18). Results: Compared to nondyskinetic patients, those with LID showed heightened [ 11 C]-(+)-PHNO binding in the D3 -rich globus pallidus. Both PD groups also showed higher binding than controls in the sensorimotor division of the striatum. In contrast, D2/3 binding in the ventral striatum was lower in patients with LID than without, possibly reflecting higher dopamine levels. Conclusions: Dopaminergic abnormalities contributing to LID may include elevated D2/3 binding in globus pallidus, perhaps reflecting D3 receptor upregulation. The findings support therapeutic strategies that target and diminish activity at D3 to prevent LID.